Research Pre-Treatment Technology and Ir Convective Drying of Pumpkin - Тukhtaev Shukhrat; Samadov Otabek; Choriev Abdusattar; Akramova Rano; Xolmurodov Bobir (Zien Journals, 2021)
The methods of primary processing of pumpkin before its final drying have been studied. Based on the analysis, a cascade drying method was selected. It is given technology of pumpkin powders.
Keywords: Pumpkin; drying; cascade; vitamins